Estudo do potencial de biossorção dos íons Cd (II), Cu (II) e Zn (II) pela macrófita Eichhornia crassipes - Lavarda, Fábio Luciano (2010)
The aim of this work was to evaluate the adsorption capacity of Eichhornia crassipes as well as to investigate on the adsorption equilibrium and kinetic of copper, cadmium and zinc divalent ions in single, binary and ternary sorption systems. In order to improve the biosorption kinetic and experimental equilibrium conditions, the temperature effect on the plant drying was tested in 30 and 50°C temperatures, while the solution temperature effect was evaluated at four controlled temperatures, ranging from 25 to 45°C. The biosorbent grain size effect was also studied, using three fractional grain sizes between 0.147 to 0.589 mm and their mixture as well. For all tests, a volume of 50 mL for metal solution (4 mEq.L-1) was added to 250 mg dry plant in 125-mL Erlenmeyer flask. The mixtures were shaken for 12 h for each temperature setting, and then, the quantity of metal in each filtrated liquid phase sample was measured by AAS. In order to obtain the equilibrium time, the adsorption experimental times were set up at several short contact times, ranging from 5 min to 48 h. On the other hand, several batch single metal sorption experiments using the E. crassipes biomass as biosorbent were also carried out using a constant volume of 50 mL metal-supplied solution (4.0 mEq.L-1) in contact with dry biomass, ranging from 20 to 550 mg. Similarly, batch multicomponent sorption experiments, with equals and different amounts of metals spiked in biosorption medium, were performed in pH 5, during a 4 h shaking time. Within the dry temperature range tested, a higher metal removal performance was achieved for a temperature of 30oC. In the interval from 25 to 45oC controlled temperatures, the highest metal removal percent was observed to occur at 30oC solution temperature. On the other hand, the metal-sorption experiments based on fractional biomass grain sizes (0.147-0.589 mm) have not shown significant differences on the metal ion removal as compared among a mixture of them and different grain sizes tested. The results of monocomponent kinetic tests have showed that the equilibrium time was achieved around 2 h, 1 h and 45 min for Zn(II), Cu(II) and Cd(II), respectively. However, 1 and 2 h equilibrium time was achieved for Zn(II) and Cd(II), respectively, in a Zn(II)-Cd(II) binary system. In similar way, 1 and 2 h equilibrium time was achieved for Cu(II) and Cd(II), respectively, in a Cu(II)-Cd(II) binary system, while it was 45 min for both Zn(II) and Cu(II) in a Zn(II)-Cu(II) binary system. From the ternary kinetic test, equilibrium time of 45 min was observed for both Zn(II) and Cd(II), while a 1h equilibrium time was observed for Cu(II). The kinetic experimental data, at 30oC and pH 5, were found to best follow the pseudo-second order kinetic model, according to the good correlation coefficient value. The single equilibrium data for each metal at pH 5 were described according to the Langmuir isotherm model, with the same maximum metal content (qmax) values around 0.6 mEq.g-1 for all metals. While, the binary sorption data were evaluated through the Langmuir-type isotherms surface and their adjustable parameters were determined by the PSO (Particle Swarm Optimization) method. From the modeling results of the binary sorption data, the maximum metal contents were: 0.49 and 0.21 mEq.g-1 for Zn(II) and Cu(II), respectively, in Zn(II)-Cu(II) system; 0.42 and 0.17 mEq.g-1 for Cu(II) and Cd(II), respectively, in Cu(II)-Cd(II) system; 0.46 and 0.17 mEq.g-1 for Zn(II) and Cd(II), respectively, in Zn(II)-Cd(II) system. While, the maximum metal content values of 0.27, 0.65 and 0.30 mEq.g-1 were obtained for Zn(II), Cu(II) and Cd(II) ions, respectively, for a ternary sorption system. The kinetic and equilibrium adsorption results suggest that the E. crassipes biomass can be used as a low-cost, alternative biosorbent in metal treatment systems of industrial effluents.